Transabdominal robotic repair of a congenital right diaphragmatic hernia containing an intrathoracic kidney: a case report. Issue 4 (December 2015) - Chen, Brendan; Finnerty, Brendan; Schamberg, Neal; Watkins, Anthony; DelPizzo, Joseph; Zarnegar, Rasa
Abstract Bochdalek diaphragmatic hernia is a rare condition and is typically diagnosed prior to adulthood. Furthermore, right-sided defects are also uncommon due to the location of the liver, but can contain colon, omentum, small bowel, or rarely the kidney. Minimally invasive laparoscopic and thoracoscopic diaphragmatic hernia repairs are associated with improved outcomes when compared to open approaches—recently, robotic-assisted repairs have been performed in children with no morbidity and minimal complications. We report a case of an 80-year-old female who presented with an enlarging right-sided Bochdalek hernia containing an acquired intrathoracic kidney that was repaired using a robotic-assisted laparoscopic transabdominal approach with mesh placement. In this case, the robotic platform's advantages included excellent visualization of the posterolateral defect and efficient suturing during mesh placement. This approach is a viable option for skilled minimally invasive surgeons; however, further studies are warranted to investigate its utility in the management of diaphragmatic hernia repair.